The Procedures of Consecutive Interpreting - Delara Siti Maulida; Andang Saehu (Linguists : Journal Of Linguistics and Language Teaching, 2022)
One of the types of interpreting is known as consecutive interpreting. Regarding the modes on how the message is rendered, the interpreter begins to interpret the utterances from the speaker only after the speaker has finished speaking. It is also believed that the procedures of consecutive interpreting involve certain stages. Thus, this small-scale research is intended to explore and discover the procedure of consecutive interpreting. Qualitative design was employed to gather and analyze the data by utilizing open-ended interview in which the interviewee was a professional interpreter. The evidence of this research revealed that there is no determined procedure to perform interpreting since every experts, researchers, and interpreters has their own set of approaches and practices for conducting interpretation consecutively. In general, the steps of consecutive interpreting consist of three stages namely pre interpreting, while interpreting and post interpreting. The procedures of consecutive interpreting are concerned with the interpreter's preparation such as preparing the material, briefing, and professional ethics, the agreement or contract between the organizer and the interpreter, strategy if interpret happened to make mistake, and, most importantly, note-taking techniques.